Enhancing community weight loss groups in a low socioeconomic status area: Application of the COM‐B model and Behaviour Change Wheel - Nia Coupe; Sarah Cotterill; Sarah Peters (Wiley, 2022)
Abstract Background Obesity rates are higher among people of lower socioeconomic status. While numerous health behaviour interventions targeting obesity exist, they are more successful at engaging higher socioeconomic status populations, leaving those in less affluent circumstances with poorer outcomes. This highlights a need for more tailored interventions. The aim of this study was to enhance an existing weight loss course for adults living in low socioeconomic communities. Methods The Behaviour Change Wheel approach was followed to design an add‐on intervention to an existing local authority‐run weight loss group, informed by mixed‐methods research and stakeholder engagement. Results The COM‐B analysis of qualitative data revealed that changes were required to psychological capability, physical and social opportunity and reflective motivation to enable dietary goal‐setting behaviours. The resulting SMART‐C booklet included 6 weeks of dietary goal setting, with weekly behavioural contract and review. Conclusion This paper details the development of the theory‐ and evidence‐informed SMART‐C intervention. This is the first report of the Behaviour Change Wheel being used to design an add‐on tool to enhance existing weight loss services. The process benefitted from a further checking stage with stakeholders.